Contribution of hot spring cyanobacteria to the mysterious deaths of Lesser Flamingos at Lake Bogoria, Kenya - Krienitz, L.; Ballot, A.; Kotut, Kiplagat; Wiegand, C.; Pütz, S.; Metcalf, J.S.; Codd, G.A.; Pflugmacher, S. (Elsevier, 2003)
Cyanobacterial mats at hot springs on the shore of the alkaline Lake Bogoria, Kenya, were investigated regarding species community and cyanobacterial toxin content. The hepatotoxins microcystin-LR, -RR, -LF and -YR, and the neurotoxin anatoxin-a were present. The mats were dominated by Phormidium terebriformis, Oscillatoria willei, Spirulina subsalsa and Synechococcus bigranulatus. The concentration of microcystins in mat samples, ranged from 221 to 845 microg microcystin-LR equivalents g(-1) DW of mat. Anatoxin-a concentrations ranged from 10 to 18 microg g(-1) DW of mat. A contribution of the cyanobacterial toxins from the hot spring mats to the mass mortalities of Lesser Flamingos is suggested by: (a), the presence of hot spring cyanobacterial cells and cell fragments, and high concentrations of the cyanobacterial hepato- and neurotoxins in flamingo stomach contents and faecal pellets; (b), observations of neurological signs of bird poisoning at the lake. Cyanobacterial toxins in stomach contents, intestine and fecal pellets were 0.196 microg g(-1) fresh weight (FW) for the microcystins and 4.34 microg g(-1) FW for anatoxin-a. Intoxication with cyanobacterial toxins could occur by uptake of detached cyanobacterial cells from the mats, as the flamingos need to drink fresh or brackish water, and to wash their feathers daily, which they do in the vicinity of the hot springs, where salinity is lower than in the main body of water of the lake.
doi: 10.1111/j.1574-6941.2003.tb01053.x.
Keywords: Anatoxin; Cyanobacteria; Hot spring; Lake Bogoria; Lesser Flamingo; Microcystin